2020
DOI: 10.1142/s1793292020500071
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Analysis of Elliptical Cantilever Device Using Flexure Method and Fabrication of Electrospun PVDF/BaTiO3 Nanocomposites

Abstract: Cantilever-based piezoelectric has been the most preferred technique for energy harvesting and sensing application due to its simple design. The energy conversion efficiency has been continuously improved by exploring alternative cantilever geometries by increasing the stress distribution on the beam surface. In this paper, we have introduced half elliptical and full elliptical profile modification in the cantilever structure to improve and uniformly distribute the stress at the beam surface. Stress distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This may indicate structural integrity or stability difficulties. Low deflection indicates a stiffer, more deform-resistant beam (Selvan, 2020).…”
Section: Theory and Modelingmentioning
confidence: 99%
“…This may indicate structural integrity or stability difficulties. Low deflection indicates a stiffer, more deform-resistant beam (Selvan, 2020).…”
Section: Theory and Modelingmentioning
confidence: 99%
“…In this regard, Sobhan added 0.8 wt.% BaTiO 3 nanoparticles to the PVDF polymer, and it was observed that the content of the β-phase increased, thereby improving the output voltage response of the sensor [6]. In 2020, Ramadoss further discovered that when 12 wt.% BaTiO 3 was doped, the electrospun PVDF/BaTiO 3 composite material had a maximum β-phase ratio of 75% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers with BaTiO 3 nanocomposite have been studied to improve the piezoelectric performance due to their high piezoelectric properties and lead-free structure. [51][52][53][54][55][56][57][58][59][60] 0.02 μW piezoelectric power output was reported using a cantilever beam type energy harvester made of PVDF/BaTiO 3 (1 Hz, 1MV resistance load). 61 The effect of BatiO 3 nanoparticle size (10, 100, 500 nm) on the piezoelectric output voltage was investigated.…”
Section: Introductionmentioning
confidence: 99%